25 W Switch-mode audio power amplifier - Laungayan, Joseph Gideon (2006)
A fully hardware-based Switch-Mode Audio Power Amplifier (SMPA) is designed. The SMPA is capable of delivering 25 W of power to an 8 omega speaker load. The modulation scheme used is unipolar pulse with modulation. A feedback circuit is designed to reduce total harmonic distortion (THD). The prototype is characterized with regard to frequency response, total harmonic distortion and efficiency.